Comparative transcriptome profiling reveals a network of differentially expressed genes in Asia II 7 and MEAM1 whitefly cryptic species in response to early infection of Cotton leaf curl Multan virus - Farooq, Tahir; Lin, Qi; She, Xiaoman; Chen, Ting; Tang, Yafei; He, Zifu (Frontiers in Microbiology, 2022)
Cotton leaf curl Multan virus (CLCuMuV) is a whitefly-vectored begomovirus that poses ramping threat to several economically important crops worldwide. The differential transmission of CLCuMuV by its vector Bemisia tabaci mainly relies on the type of whitefly cryptic species. However, the molecular responses among different whitefly cryptic species in response to early CLCuMuV infection remain elusive. Here, we compared early-stage transcriptomic profiles of Asia II 7 and MEAM1 cryptic species infected by CLCuMuV. Results of Illumina sequencing revealed that after 6 and 12 hours of CLCuMuV acquisition, 153 and 141 genes among viruliferous (VF) Asia II 7, while 445 and 347 genes among VF MEAM 1 whiteflies were differentially expressed compared with aviruliferous (AVF) whiteflies. The most abundant groups of differentially expressed genes (DEGs) among Asia II 7 and MEAM1 were associated with HTH-1 and zf-C2H2 classes of transcription factors (TFs), respectively. Notably, in contrast to Asia II 7, MEAM1 cryptic species displayed higher transcriptional variations with elevated immune-related responses following CLCuMuV infection. Among both cryptic species, we identified several highly responsive candidate DEGs associated with antiviral innate immunity (alpha glucosidase, LSM14-like protein B and phosphoenolpyruvate carboxykinase), lysosome (GPI-anchored protein 58) and autophagy/phagosome pathways (sequestosome-1, cathepsin F-like protease), spliceosome (heat shock protein 70), detoxification (cytochrome P450 4C1), cGMP-PKG signaling pathway (myosin heavy chain), carbohydrate metabolism (alpha-glucosidase), biological transport (mitochondrial phosphate carrier) and protein absorption and digestion (cuticle protein 8). Further validation of RNA-seq results showed that 23 of 28 selected genes exhibited concordant expression both in RT-qPCR and RNA-seq. Our findings provide vital mechanistic insights into begomovirus-whitefly interactions to understand the dynamics of differential begomovirus transmission by different whitefly cryptic species and reveal novel molecular targets for sustainable management of insect-transmitted plant viruses.